Confidence intervals for the regression coefficient in a simple regression model with a balanced two-fold nested error structure. Issue 17 (1st September 2016) - Park, Dong Joon; Yoon, Min
ABSTRACT: In applications using a simple regression model with a balanced two-fold nested error structure, interest focuses on inferences concerning the regression coefficient. This article derives exact and approximate confidence intervals on the regression coefficient in the simple regression model with a balanced two-fold nested error structure. Eleven methods are considered for constructing the confidence intervals on the regression coefficient. Computer simulation is performed to compare the proposed confidence intervals. Recommendations are suggested for selecting an appropriate method.